(untitled) (Research, Society and Development, 2020)
The work aims to discuss the importance of public policy through a philanthropic hospital for the region of Alexandria / RN. Public policies are guidelines built for the benefit of the population. The research carried out is exploratory in nature and the method used was qualitative and quantitative, using two instruments: a questionnaire with the patients and an interview with two nurses who are part of the hospital administration, to analyze the answers, the questionnaire was analyzed by simple statistics and the interview by content analysis The results analyzed were verified that the hospital has a very high degree of importance for the city of Alexandria / RN and for the region surrounding the hospital and that public policies do not hinder the operation of the hospital but the negligence of governmental actors can disturb the hospital.